2001
DOI: 10.1007/bf03168817
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate self-poisoning in an Irish county hospital

Abstract: Deliberate self-poisoning remains a significant problem. Paracetamol and alcohol use are particularly marked in this population. The combination of tricyclic antidepressant drugs and alcohol were the most dangerous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…Our data do not agree with some recent findings indicating NSAIDs (particularly paracetamol) as drugs frequently used for parasuicidal purposes [4,6,18]. …”
Section: Discussioncontrasting
confidence: 99%
“…Our data do not agree with some recent findings indicating NSAIDs (particularly paracetamol) as drugs frequently used for parasuicidal purposes [4,6,18]. …”
Section: Discussioncontrasting
confidence: 99%
“…It was reported that 50% of adult poisonings were with 2-3 agents by Mc Mahon et al (22). Fifty three percent of poisonings with drugs were with analgesics, 31% with multiple drugs (vitamin, antihistamines, antibiotics, digestive system drug, antitussive) and 16% with psychiatric drugs (tricyclic antidepressants, SSRIs).…”
Section: Discussionmentioning
confidence: 99%
“…A review of 16 studies that included data on acute alcohol use and suicide attempts found that on average, 40% of attempters had used alcohol, with some estimates ranging as high as 73%, similar rates of alcohol use were found among completed suicides (Cherpitel et al, 2004). Three studies directly measuring blood alcohol level (Borges and Rosovsky, 1996; McMahon and McGarry, 2001; Suokas and Lonnqvist, 1995) found a significant association between suicide attempts and recent alcohol consumption. There is some evidence for a dose–response relationship whereby the more alcohol consumed, the greater the risk of suicidal behavior (Borges and Rosovsky, 1996).…”
Section: Discussionmentioning
confidence: 99%